Human’s identity and condition - Grochowska, Irena (Studia Ecologiae et Bioethicae, 2005)
Human aims for internal integrity and unison at all levels of human are identity and all dimensions of human existence. According to Rull integrity is a gift from God, but also a task for everybody, only possible when a human being is open for autotranscendency. Unity of mankind is based on condition. The key word condition means that a human being is not neutral. The conditions indicates limitations and burdens of human being, although more and more frequently modern man tries to deny it, defining by himself who he wants to be and taking the place of God. Modern individualism is a lonely following of traditional utopia of society. Delsol claims that the most certain thing, which we can say about a man, is the existence of his condition, which acceptance is possible under condition of leaving the theory of ruling. We are not independent from our condition, we can free ourselves from it like we cannot deny the way we look, the condition is like terminal illness. A person’s dignity grows from the wound of finiteness. Greatness of man is about receiving and solving problems, a constant struggle, not owing a panacea for all human problems. A man who rejects reality, wanting to create his own self loses form and falls. To realise about the human condition would mean leaving the possibility of existence, potentiality for act. Human being who does not accept the human condition becomes undefined, he does not know his identity, he is restricted to mass, to biological body, he looks after it, improves it looking for fulfilment. But identity requires defining, one cannot be oneself if one does not know what one should be.